2023
DOI: 10.1002/cctc.202201150
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Near Ambient Pressure Activity of Intermetallic NiZn/TiO2 Catalyst for CO2 Conversion to Methanol

Abstract: NiÀ Zn pair is predicted through descriptor-based studies to be conducive for CO 2 hydrogenation. In this study, NiZn (1 : 1) intermetallics supported on TiO 2 is identified as a potential candidate for near ambient pressure activity. The effect of reduction temperature on the catalyst textural properties as well as on CO 2 to methanol reduction are explored. Structural and microscopic studies provide clear evidence of phase evolution of NiZn alloy with increasing reduction temperatures, along with phase varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, the formation of methanolic species was observed by in‐situ IR characterization suggested that methanol formation from CO 2 could be possible in the reaction carried out at atmospheric pressure. It was concluded that ZnNi intermetallics could be the active phase for methanol formation at low pressures, which is corroborated by in situ IR studies, where methoxy species were detected even at ambient pressure [149] . However, with regard to ZnNi intermetallic compound, since this compound is not stable under MSR conditions, [151] it is very unlikely that ZnNi intermetallics could be stable under MeOH synthesis conditions.…”
Section: Advances In Intermetallic Catalysts For Methanol Synthesis F...mentioning
confidence: 84%
See 4 more Smart Citations
“…Interestingly, the formation of methanolic species was observed by in‐situ IR characterization suggested that methanol formation from CO 2 could be possible in the reaction carried out at atmospheric pressure. It was concluded that ZnNi intermetallics could be the active phase for methanol formation at low pressures, which is corroborated by in situ IR studies, where methoxy species were detected even at ambient pressure [149] . However, with regard to ZnNi intermetallic compound, since this compound is not stable under MSR conditions, [151] it is very unlikely that ZnNi intermetallics could be stable under MeOH synthesis conditions.…”
Section: Advances In Intermetallic Catalysts For Methanol Synthesis F...mentioning
confidence: 84%
“…[148] The efficiency of the ZnNi (1 : 1) intermetallic catalysts supported on TiO 2 was studied by Dongapure et al [149] The TiO 2 support was commercial P25 TiO 2 material consisting of rutile and anatase, which is known for activating CO 2 through formate pathway. [149] In comparison with ZnPd intermetallic catalyst supported on TiO 2 anatase phase, [70] the formation of the ZnNi intermetallics occurred at much higher temperature of 550 °C, as it was confirmed by XRD and HAADF-STEM microscopic studies. [149] Since the ZnNi intermetallic particles were found to be in close proximity to ZnO NPs, it was concluded that the reaction might occur at interphase between ZnNi and ZnO.…”
Section: Other Cu-and Ni-containing Intermetallicsmentioning
confidence: 99%
See 3 more Smart Citations